(untitled) (Edad Media. Revista de Historia, 2023)
The agreement to plan the conquest of Almería established in 1146 between the Republic of Genoa and King Alfonso VII of Castile is known through various parchment documents scattered across different archives, from Genoa to Saint Petersburg.The aim of this paper is to clarify the genesis and textual tradition of these documents. Diplomatic analysis allows us to reconstruct a complex sequence that starts with a draft, follows with a protocol and ends with an authentic copy. This set of documents represents an exceptional testimony of the issuing of charters in twelfth-century chanceries, and shows the development of issuing procedures as meticulous as complex, which have generally left very few traces in historical archives.